Synergistic cooperation between two ClpB isoforms in aggregate reactivation - Nagy, Maria (2009)
Bacterial AAA+ ATPase ClpB cooperates with DnaK during reactivation of aggregated proteins. The ClpB-mediated disaggregation is linked to translocation of polypeptides through the channel in the oligomeric ClpB. Two isoforms of ClpB are produced in vivo: the full-length ClpB95 and ClpB80 which does not contain the substrate-interacting N-terminal domain. The biological role of the truncated isoform ClpB80 is unknown. We found that resolubilization of aggregated proteins in E. coli after heat-shock and reactivation of aggregated proteins in vitro and in vivo occurred at higher rates in the presence of ClpB95 with ClpB80 than with ClpB95 or ClpB80 alone. Combined amounts of ClpB95 and ClpB80 bound to aggregated substrates were similar to the amounts of either ClpB95 or ClpB80 bound to the substrates in the absence of another isoform. The ATP hydrolysis rate of ClpB95 with ClpB80, which is linked to the rate of substrate translocation, was not higher than the rates measured for the isolated ClpB95 or ClpB80. We postulate that a reaction step that takes place after substrate binding to ClpB and precedes substrate translocation is rate-limiting during aggregate reactivation and its efficiency is enhanced in the presence of both ClpB isoforms. Moreover, we found that ClpB95 and ClpB80 form hetero-oligomers which are similar in size to the homo-oligomers of ClpB95 or ClpB80. Thus, the mechanism of functional cooperation of the two isoforms of ClpB may be linked to their hetero-association. Our results suggest that the functionality of other AAA+ ATPases may be also optimized by interaction and synergistic cooperation of their isoforms.